Ski touring on groomed slopes: Analyzing opportunities, threats and areas of conflict associated with an emerging outdoor activity. (September 2022) - Happ, Elisabeth; Schnitzer, Martin
Abstract: Ski touring on groomed slopes (= slope ski touring) has experienced a boom in recent years. However, investigations in terms of slope ski touring and ski tourers are scarce. Thus, there has been a call for more research that also encompasses stakeholders' opinions. This study aims to provide deeper insights into the trend of slope ski touring along with associated risks and opportunities as well as areas of conflict. Two qualitative studies were conducted: Study A covered interviews with 14 slope ski touring experts; study B surveyed 14 ropeway industry experts, who represented the main stakeholder groups. The results revealed that slope ski touring is an emerging trend (RQ1), since there is an increased number of ski tourers in ski resorts. The growing numbers of slope ski tourers are giving rise to economic, health and social opportunities. Both expert groups confirmed that this emerging trend is also associated with certain burden—relating to safety issues due to overcrowding on the one hand and to financial burdens for the ropeway infrastructure (RQ2) on the other. The studies also showed that there are areas of conflict, for example, due to a lack of ascent tracks, adverse behavior leading to rule violations and scarce parking. Furthermore, conflicts could be noted between different groups on the mountain (especially alpine skiers vs. slope ski tourers; slope ski tourers vs. mountain ropeway operators); eventually, ropeway operators have often been facing the financial burden of receiving no income from slope ski tourers. Solutions that could nip the burdens, risks and conflicts are still few and answers are missing (RQ3 and RQ4). Management Implications: For managers it is important to understand that ski touring on slopes is the European Alps an emerging trend with increasing economic, health and social relevance. The interests of users have changed over time. Areas of conflict are areas with a risk of collision with other athletes or ropeway operators. Ski touring on slopes offer new opportunities for smaller specialized ski resorts and their gastronomic services. Experts recommend separate ascent lanes for this activity, to enhance the safety. Financial contributions by this group of athletes are still an open question.